DIFFERENCE BETWEEN ZIRCONIUM CROWNS AND STAINLESS STEEL CROWNS IN PREMOLAR PROSTHETICS (American Journal of Pedagogical and Educational Research, 2023)
One of the reasons for the rejection of the use of CAD/CAM technologies in dentistry is reports of the insolvency of all-ceramic frame restorations made of polycrystalline ceramics based on zirconium dioxide and chipped veneers [1, 2]. The discrepancy in the recommendations for the manufacture of frame all-ceramic restorations raises a number of questions. Sandblasting is still widely used to improve surface roughness, strengthen bonding between the veneer and the frame and increase the strength of the connection during cementing.